“For Heaven to Bend to the Earth” or the Christian Thought in Vaižgantas’s Journalism - Vanagaitė, Gitana (Respectus Philologicus, 2021)
Literary theology, which began to form in the second half of the 20th century, opened up new possibilities for linking religion, literature, and personal experience. The journalistic articles of Juozas Tumas-Vaižgantas (1869–1933) show that, on the one hand, he understood the world in a crystcentric way. On the other hand, Vaižgantas’s thought was also shaped by modernity and the time he lived in, which inclined him to reject religion. By analysing Vaižgantas’s journalistic articles and letters to his relatives, this article argues that the writer’s modernity rests on the interaction of the two realities: the eternal reality of God and the temporal reality of man. Having managed to combine these two realities with his human presence, Vaižgantas has opened up to our culture the dynamics of this interaction, in which the Christian self-restraint and modern consciousness, acting as complementary parts, become an act of self-creation founded on rational will, which in turn is associated with self-control, moderation, determination, and renunciation of egoism.